Short-chain fatty acid-producing bacterial strains attenuate experimental ulcerative colitis by promoting M2 macrophage polarization via JAK/STAT3/FOXO3 axis inactivation - Hailan Zhao; Youlian Zhou; Jing Xu; Yong Zhang; Hong Wang; Chong Zhao; Hongli Huang; Jing Yang; Chen Huang; Yingfei Li; Lisheng Wang; Yuqiang Nie (Journal of Translational Medicine, 2024)
Abstract Background Patients with inflammatory bowel disease (IBD), dysbiosis, and immunosuppression who receive fecal microbiota transplantation (FMT) from healthy donors are at an increased risk of developing bacteremia. This study investigates the efficacy of a mixture of seven short-chain fatty acid (SCFA)-producing bacterial strains (7-mix), the resulting culture supernatant mixture (mix-sup), and FMT for treating experimental ulcerative colitis (UC) and evaluates underlying mechanisms. Methods Utilizing culturomics, we isolated and cultured SCFA-producing bacteria from the stool of healthy donors. We used a mouse model of acute UC induced by dextran sulfate sodium (DSS) to assess the effects of 7-mix, mix-sup, and FMT on intestinal inflammation and barrier function, microbial abundance and diversity, and gut macrophage polarization by flow cytometry, immunohistochemistry, 16S rRNA gene sequencing, and transwell assays. Results The abundance of several SCFA-producing bacterial taxa decreased in patients with UC. Seven-mix and mix-sup suppressed the inflammatory response and enhanced intestinal mucosal barrier function in the mouse model of UC to an extent similar to or superior to that of FMT. Moreover, 7-mix and mix-sup increased the abundance of SCFA-producing bacteria and SCFA concentrations in colitic mice. The effects of these interventions on the inflammatory response and gut barrier function were mediated by JAK/STAT3/FOXO3 axis inactivation in macrophages by inducing M2 macrophage polarization in vivo and in vitro. Conclusions Our approach provides new opportunities to rationally harness live gut probiotic strains and metabolites to reduce intestinal inflammation, restore gut microbial composition, and expedite the development of safe and effective treatments for IBD.